Biosurfactant-producing bacteria counteract hydrocarbon-driven delay of sulfolane migration in groundwater - Erica Pensini; Caitlyn Hsiung; Alejandro G. Marangoni (Discover Water)
Abstract Sulfolane is a worldwide water-soluble pollutant, which typically migrates rapidly in impacted aquifers, with risks to water bodies and drinking water wells. Sulfolane migration may be delayed in sites co-polluted by hydrocarbons, which move more slowly and in which sulfolane partitions. However, when bacteria such as Pseudomonas aeruginosa aerobically biodegrade hydrocarbons and sulfolane, they generate biosurfactants (such as rhamnolipids). These enclose sulfolane within micelles and droplets, as seen by optical microscopy, and hamper its partitioning into hydrocarbons, as shown by Fourier transform infrared spectroscopy. Therefore, biosurfactants have the potential to accelerate sulfolane migration in groundwater, compared to scenarios where biosurfactant-producing bacteria are absent. These findings will aid safe management of impacted sites, where aerobic bacterial bioremediation is used for pollutant clean-up. When aerobic bacterial activity is promoted to enable pollutant biodegradation, sulfolane migration may accelerate before clean-up is complete, begging for careful monitoring of pollutant plumes. Graphical Abstract